PCR Array Technology in Biopsy Samples Identifies Up-Regulated mTOR Pathway Genes as Potential Rejection Biomarkers After Kidney Transplantation - Legaz, Isabel; Bernardo, María Victoria; Alfaro, Rafael; Martínez-Banaclocha, Helios; Galián, Jose Antonio; Jimenez-Coll, Victor; Boix, Francisco; Mrowiec, Anna; Salmeron, Diego; Botella, Carmen; Parrado, Antonio; Moya-Quiles, María Rosa; et al. (Frontiers in Medicine, 2021)
Background: Antibody-mediated rejection (AMR) is the major cause of kidney transplant failure. The donor-specific human leukocyte antigen (HLA) antibody (DSA) response to a renal allograft is not fully understood. mTOR complex has been implicated in accommodation or rejection transplant and integrates responses from a wide variety of signals. The aim of this study was to analyze the expression of the mTOR pathway genes in a large cohort of kidney transplant patients to determine its possible influence on the transplant outcome. Methods: A total of 269 renal transplanted patients monitored for DSA were analyzed. Two groups of patients were considered, with rejection (+DSA/+AMR) and without rejection (+DSA/−AMR and –DSA, controls). Total RNA was extracted and isolated from kidney biopsies and reverse transcribed to cDNA was realized. Human mTOR-PCR array technology was used to determine the expression of 84 mTOR pathway genes. STRING and REVIGO softwares were used to create gen-gen interaction and assign a molecular function. Results: A differential expression of the mTOR pathway related genes was detected in the two groups. An over-expressed transcript(≥5-fold) were found toAKT1S1, DDIT4, EIF4E, HRAS, IGF1, INS, IRS1, PIK3CD, PIK3CG, PRKAG3, PRKCB (>12-fold), PRKCG, RPS6KA2, TELO2, ULK1 and VEGFC in rejection group respect to non-rejection kidney group. AKT1S1 transcripts were more expressed in +DSA/−AMR biopsies versus +DSA/+AMR. The main molecular functions of up-regulated gene products were mainly phosphotransferase activity, insulin-like grown factor receptor and ribonucleoside phosphate binding. Under-expressed transcript (≥5-fold) were also found in rejection respect to without rejection (VEGFA (>15-fold), RPS6, RHOA. The molecular function of down-regulated gene products was also analyzed and they were mainly protein kinase activity and carbohydrate derivative binding proteins. Conclusions: A higher number of over-expressed of the mTOR pathway genes than down-expressed transcript in reject kidney biopsies (+DSA/+AMR) respect to controls. Besides, the molecular function of both types of transcripts (over/down expressed) is different. Given these findings, further studies are needed to determine if variations in gene expression profiles can act as predictors of graft loss, also a greater understanding of the mechanisms of action of the involved proteins would be necessary.